(untitled) (American Journal of Islam and Society, 2014)
This book surveys the development of literal meaning and literalism in Islam and Islamic legal theory (uṣūl al-fiqh) in particular. The term literal meaning refers to the meaning that a text is believed to hold “in itself” by virtue of the sound-meaning relationships of words that were “coined” (waḍ‘) at some point in time. Although Muslim debates on how words were coined (see second chapter) are quite interesting and at times entertaining, the origin of language was secondary to the language’s actual existence. In other words, legal theorists contended that the establishment of the “sound-meaning connection” was more important than who established it and when. Literalism, the other focus of the book, is the view that Islamic law privileges literal meaning. As Gleave explains in his first chapter, literalism sees literal meaning as having an “advantage” over allusion, metaphor (majāz), and other kinds of meaning because it holds a “higher level of epistemological security” (p. 1). Detecting the author’s intended meaning, although ideal, is fraught with uncertainties for it involves discerning another person’s intentions. In other words, for legal theorists, the literal can be established through a strict science of language and more importantly functions as a “starting point” for understanding texts which gives it a central role in hermeneutics. Even if the literal meaning is shown not to be the author’s intended meaning, it is nevertheless essential for controlling and understanding the linguistic and semantic parameters of a word and the overall text in question. Gleave makes it clear that his purpose is not to establish whether or not there is such a thing as literal meaning but instead to demonstrate the importance of its various concepts and the role they played for Muslim legal theorists of all sects as understanding how a language system works is key to grasping “God’s meaning when he addresses (khiṭāb) his servants” (p. 35). The first two chapters are useful introductions to concepts of literal meaning in legal theory. The third chapter, where the author traces one of the early concepts and uses of literal meaning in Qur’anic exegesis, delineates its early historical emergence in Islamic thought. This is significant for Islamic law and legal theory as later Muslim legal hermeneutics had “imprints” of the debates that took place in scriptural exegesis where literal meaning was often identified (e.g., through establishing what a word “literally” meant by tracing its ...